Growth Period of Porang (Amorphophallus onchophyllus P.) Through Tubber Cut and Inorganic Fertilizer Treatment - F. Deru Dewanti; Ramdan Hidayat; Puji Lestari Tarigan (Jurnal Penelitian Pendidikan IPA, 2023)
Porang (Amorphophallus onchophyllus) has many benefits for industry and health, because of the high content of glucomannan in its tubers. Porang needs to be developed, but the problem is getting a uniform source of tuber seeds. To get the uniform tuber seeds by dividing them. This study aims to get a uniform source of tuber seeds. This study was conducted in the field and laboratory. The experiment was arranged in a CRD. There are two factors, in seed tuber division: U1= Intact tuber, U2=Tuber cut in 2, U3=Tuber cut in 3 parts, and U4=Tubers cut into 4 parts. The second factor is fertilizer consisting of Urea, Za, and Phonska. The results of the combined treatment between tuber division and fertilizer treatment showed no significant interaction in all observed parameters. The seed tuber division treatment affects the bud break time, plant height, stem diameter, and canopy width, only at the beginning of growth. U1 gives the highest growth. The various fertilizer treatments only had a significant effect on plant height and stem diameter at 7 and 8 WAP. The treatment of splitting tuber seeds can replace intact tubers to be used as Porang tuber seeds